Outcomes of children with hepatoblastoma who underwent liver resection at a tertiary hospital in China: a retrospective analysis - Jiahao Li; Huixian Li; Huiying Wu; Huilin Niu; Haibo Li; Jing Pan; Jiliang Yang; Tianbao Tan; Chao Hu; Tao Xu; Xiaohong Zhang; Manna Zheng; et al. (BMC, 2020)
Abstract Background To report the outcomes of hepatoblastoma resected in our institution. Methods We diagnosed 135 children with hepatoblastoma at our institution between January 2010 and December 2017. Patients who underwent liver resection were included for analysis. However, patients who abandoned treatment after diagnosis were excluded from analysis, but their clinical characteristics were provided in the supplementary material. Results Forty-two patients abandoned treatment, whereas 93 patients underwent liver resection and were included for statistical analysis. Thirty-six, 23, 3, and 31 patients had PRETEXT stages II, III, IV, and unspecified tumours, respectively. Seven patients had ruptured tumour; 9 had lung metastasis (one patient had portal vein thrombosis concurrently). Sixteen patients underwent primary liver resection; 22, 25, and 30 patients received cisplatin-based neoadjuvant chemotherapy and delayed surgery, preoperative transarterial chemoembolization (TACE) and delayed surgery, and a combination of cisplatin-based neoadjuvant chemotherapy, TACE, and delayed surgery, respectively. Forty patients had both PRETEXT and POST-TEXT information available for analysis. Twelve patients were down-staged after preoperative treatment, including 2, 8, and 2 patients from stages IV to III, III to II, and II to I, respectively. Ten patients with unspecified PRETEXT stage were confirmed to have POST-TEXT stages II (n = 8) and I (n = 2) tumours. Seven tumours were associated with positive surgical margins, and 12 patients had microvascular involvement. During a median follow-up period of 30.5 months, 84 patients survived without relapse, 9 experienced tumour recurrence, and 4 died. The 2-year event-free survival (EFS) and overall survival (OS) rates were 89.4 ± 3.4%, and 95.2 ± 2.4%, respectively; they were significantly better among patients without metastasis (no metastasis vs metastasis: EFS, 93.5 ± 3.7% vs 46.7 ± 19.0%, adjusted p = 0.002. OS, 97.6 ± 2.4% vs 61.0 ± 18.1%, adjusted p = 0.005), and similar among patients treated with different preoperative strategies (chemotherapy only vs TACE only vs Both: EFS, 94.7 ± 5.1% vs 91.7 ± 5.6% vs 85.6 ± 6.7%, p = 0.542. OS, 94.1 ± 5.7% vs 95.7 ± 4.3% vs 96.7 ± 3.3%, p = 0.845). Conclusion The OS for patients with hepatoblastoma who underwent liver resection was satisfactory. Neoadjuvant chemotherapy and TACE seemed to have a similar effect on OS. However, the abandonment of treatment by patients with hepatoblastoma was common, and may have biased our results.